Humans as Objects of Education (Analysis of the Tafsir of the Qur'an Surah Ar Rahman Verses 1-4) - Nurul Hanifah (Mazidah: Journal Of Educational Research, 2025)
The aim of writing this paper is to interpret Surah Ar Rahman verses 1-4 in the form of knowing the contents of the verses listed and as a lesson for us in studying the science of Al-Qur'an interpretation and to apply or practice in the real world. The background to this writing is because in this day and age, especially in terms of speaking. Every human being must be able or clever at conversing, but when talking to others, by using the knowledge in the Qur'an that has been studied, then that person must know how to speak well and correctly which has faith, morals and morals as a good Muslim human being because everything based on the Koran is true because it comes from Allah. In this interpretation of Surah Ar Rahman verses 1-4, hopefully God's creatures can understand how to speak well and correctly according to the provisions stated in the Qur'an and can be applied to everyday life.